Development of balance in children with visual deprivation during adaptive physical education classes - Kielevainen L.M. ,; Khizhkin E.A. ,; Karpina L.V. , (Theory and Practice of Physical Culture, 2023)
Abstract Objective of the study was to compare indicators of balance development in children with visual deprivation engaged in different types of adaptive physical education - goalball or ice skating in extracurricular activities. Methods and structure of the study. During the comparison, two experimental groups were formed, each with nine children with visual deprivation of a different nature. Each group had one participant with total blindness. The age of the participants is 8-12 years. As part of extracurricular activities, group No. 1 attended goalball classes, group No. 2 attended skating classes. The dynamics of the development of static balance were determined using the Romberg heel-toe test with open eyes, the Romberg test with closed eyes, and the E.Ya. Bondarevsky test. The dynamics of development of dynamic balance was determined using the test according to V.I. Lyakh. Results and conclusions. At the end of the scientific work, an analysis of the results of performing the Romberg test with eyes closed showed almost the same increase in indicators in both groups - 39.6% in children involved in goalball and 39.1% in children involved in skating, in terms of the Romberg heel-toe test There is a significant difference: among children involved in ice skating, the increase was 116.6%, while among children involved in goalball - 52.9%. Results in the test by E.Ya. Bondarevsky indicate a greater increase in indicators in the group of children involved in goalball than in the group of children involved in skating: 160% and 133%, respectively. According to the results of the test to determine dynamic balance (V.I. Lyakh), in group No. 1 there is an increase of 37.5%, in group No. 2 - 36.8%, however, there is a statistically significant decrease in the average value only in group No. 1. The results of the study can be applied in the development of rehabilitation programs to develop coordination (balance) for children with visual deprivation.